Labour Mobility and the Portability of Social Rights in the EU - Anna Cristina d'Addio; Maria Chiara Cavalleri (Center for Economic Studies and ifo Institute (CESifo), 2013)
The paper first discusses the main sources of concern for people in the perspective of professional mobility abroad as they result from the analysis of the Eurobarometer survey, wave 75.1 of 2011. Second, it tests whether portability of social security within Europe is a determinant of intra-EU mobility. It does this by using Eurobarometer data for the estimation of a multinomial logit model with a propensity matching scheme in which those that made the experience of social security transfer in the past (either difficult or easy) are compared to those that never had such experience. The results suggest that an easy experience with the transfer of social security across countries may increase the propensity to move abroad for professional reasons. In contrast, difficulties are likely to negatively affect mobility incentives. The sign of the effect is stable across countries, but intensity varies depending on the group of countries considered being them EU-15 or EU-12.
Keywords: J61; J62; H55; C25; 330; labour mobility; portability; social protection; European Union